(untitled) (Research, Society and Development, 2022)
Objective: To verify the distribution of cases of Congenital Syphilis (CS) diagnosed in children under one year of age in Brazilian regions and to investigate sociodemographic and clinical aspects. Materials and methods: This is a descriptive, retrospective study with a quantitative approach, developed from secondary data from 2011 to 2020 in Brazil. Data were obtained through the Notifiable Diseases Information System. The incidence rates of SC were calculated by the constant 1,000. Results: A total of 188,268 cases of CS were reported in the study period, showing an ascending series year by year, with a subsequent reduction in the last two years (average incidence of 29.7 cases/1,000 live births). The total number of cases was distributed by regions, and the Southeast region had the highest number of notifications (83,317 cases) and the average incidence rate (7.2 cases/1,000 live births) (p<0.05). Most pregnant women were between 20 and 29 years old, 53.7%, with a low level of education 18.2% and 48.7% of mixed race, 79.6% had prenatal care, 56.0% were diagnosed with syphilis during prenatal care and 51.7% had inadequate treatment. Most children with CS were less than seven days old 96.7% and 92.6% were diagnosed with recent CS. Conclusion: The high incidence of CS reported throughout Brazil, in the period considered, requires the need to train health professionals to perform prenatal care so that it is instituted early and timely treatment is carried out.